Bagaimana Media Memberitakan Produk Pangan? Analisis Isi Artikel Media Daring Tentang Susu Kental Manis - Anshari, Dien; Wachyu, Mochamad; Qatrunnada, Nadia H; Syafiq, Ahmad (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background: The news media can shape public agenda and perspective on a particular issue. Objective: To analyze how online media portrayed sweetened condensed milk (SKM) as a food product. Methods: We content analyzed all articles about SKM from 4 online media in Indonesia published in 2016-2017. All articles were reliably coded for frequency, media sources, type, tone, and frames. Results: From a total of 375 articles found, 24 were framed positively, 34 were framed negatively, while the rest were neutral. SKM was positively framed as it enhances flavor, affordable, high usage, and a source of energy and protein. While SKM was framed negatively because of high sugar and fat content, is not dairy products, and can cause diabetes, obesity, digestive problems, and tooth decay. Some negative frames of SKM were only used in 2017. Timeline for articles with negative frames appear to have a certain pattern and not based on a specific case. Conclusion: In framing SKM, online news media seems to ignore the principles of journalism such as impact (significance), urgency, and factual verification. Further research is needed to investigate the political economy of online media in telling stories about food products.